The Effect of the Addition of Red Kidney Bean Skin Powder (Phaseolus vulgaris L.) on the Physical, Chemical, and Organoleptic Characteristics of Red Kidney Bean Tempeh - Novelina Novelina; Linda Wati; Purnama Dini Hari; Qurrata A'yun (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Red kidney bean tempeh production is generally made by beans without the epidermis, but in this study, the epidermis was removed from the red beans, dried and powdered, and then added back to the tempeh red beans. This research aims to determine the effect of adding red bean skin powder on the physical, chemical, and organoleptic properties of the tempeh produced. The design used in this research was a completely randomized design (CRD) with five treatments and three replications. The treatment in this research was wet peeled red beans without skin (control) and the addition of red kidney bean skin powder starting from 15%, 30%, 45%, and 60% in red kidney beans before fermentation. Research data was analyzed using ANOVA and Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results of this research showed that the treatments caused significantly different texture values, water content, ash content, protein content, crude fiber content, and iron (Fe) content, but no significant differences in fat content or carbohydrate content. The best treatment based on physical, chemical and organoleptic analysis was treatment C (addition of 30% red bean skin powder) with an average texture value of 2.01 N/cm2, water content of 61.63%, ash content of 0.72%, protein content of 15.83%, fat content of 1.51%, carbohydrate content of 20.30%, crude fiber content of 6.95%, iron content of 5.00 mg/g coliform content of 0.32 APM/g, and salmonella negative/g. The organoleptic test values were color 6.20 (preferred), texture 6.15 (preferred), taste 4.05 (less preferred), and aroma 4.45 (less preferred).